Daily requirement of softgel thyroxine is independent from gastric juice pH - Virili, Camilla; Capriello, Silvia; Stramazzo, Ilaria; Brusca, Nunzia; Santaguida, Maria Giulia; Gargano, Lucilla; Bagaglini, Maria Flavia; Bruno, Giovanni; Severi, Carola; Centanni, Marco (Frontiers in Endocrinology, 2022)
Background Softgel levothyroxine (LT4) preparation showed a better in vitro dissolution profile at increasing pH as compared to tablet LT4 preparation. Clinical studies suggested a better performance of softgel LT4 preparation in patients with gastric disorders but whether this finding is related to gastric juice pH variation in vivo is not known. Methods Twenty-eight hypothyroid patients (24F/4M; median age=50 treated with tablet LT4 (median dose= 1.65 µg/kg/day) and with stable thyroid stimulating hormone (TSH) values on target (<0.8-2.5> mU/l) have been shifted to softgel LT4 preparation. The dose of softgel LT4 has been titrated to obtain a similar individual serum TSH value. All subjects followed a specific treatment schedule, taking LT4 in fasting condition and then abstaining from eating or drinking for at least 1 hour. Owing to the presence of long-lasting dyspepsia or of already known gastric disorders, all patients underwent endoscopy, upon informed consent. Gastric juice has been collected during endoscopy to measure gastric pH. Then we plotted the dose of LT4 with the gastric pH obtained in vivo, before and after the switch tablet/softgel preparation in all patients. Results Upon the switch tablet/softgel preparation, the therapeutic LT4 dose was very slightly reduced (-6%) in the whole sample. However, the individual variations revealed the existence of two populations, one without any dose reduction (A) and the other showing a dose reduction >20% (B). Upon matching with the actual gastric pH, patients with normal pH (A: n=17; 14F/3M, median 1.52) no showed a lower softgel LT4 requirement. Instead, among patients with reduced gastric acid production (B: n=11; 10F/1M, median pH 5.02) the vast majority (10/11; 91%, p<0.0001) benefited from a lower dose of softgel LT4 (median = -23%, p<0.0001). Interestingly, the dose of LT4 in tablet correlated with pH value (Spearman’s ρ =0.6409; p = 0.0002) while softgel dose was independent from gastric juice pH (Spearman’s ρ =1.952; p = 0.3194). Conclusions These findings provide evidence that softgel LT4 preparation is independent from the actual gastric pH in humans and may represent a significant therapeutic option in patients with increased LT4 requirement, owed to disorders impairing the gastric acidic output.